MENGUKUR PELUANG DAN ANCAMAN BONUS DEMOGRAFI TERHADAP KUALITAS SUMBERDAYA MANUSIA DALAM PEMBANGUNAN EKONOMI DI BANDAR LAMPUNG - Astuti, Hesti Widi; Soetarmiyati, Nani (Jurnal Bisnis Darmajaya, 2016)
Currently the population of Bandar Lampung changes and growth over time which causes a shift in the population age structure of the young into adulthood. Projections can help predict when Bandar Lampung population of productive age with the smallest ratio of dependency load-called demographic bonus. Opportunities from the demographic bonus can be seen from the structure of the population in Bandar Lampung, including a young population structure. It can be seen from the large number of young people (0-14 years), although the number of births has decreased when compared with five years ago and life expectancy is increasing is characterized by an increasing number of elderly. Contribution of research to be achieved is 1) Lampung city government could control the number of births so that when the number of births is decreasing, population growth slowed from a young age population of productive age. With a population that must be borne by little, the city of Bandar Lampung obtain a window of opportunity to push its economy more quickly. This can only be achieved if the government can create social and economic policies right. 2) To promote economic growth in the city of Bandar Lampung, the government needs to suppress the rate of population growth. One of them with a re-run family planning program. 3) The increase in the productive age of the demographic bonus will increase the income of the productive age group so that the middle class population in Bandar Lampung increased. This bias is obtained by using the techniques of data collection through survey by distributing questionnaires to people in 20 Sub City Lampung processed data through path analysis that can measure the opportunities and threats bonus Demographics in improving the quality of human resources to promote economic development in Bandar Lampung.Keywords: Bonus Demographics, Human Sumberday Quality, Economic Development